Preclinical pharmacokinetic characterization of an adipose tissue-targeting monoclonal antibody in obese and non-obese animals. Issue 8 (17th November 2017) - Rajan, Sharmila; Mandikian, Danielle; Baruch, Amos; Gelzleichter, Thomas R.; Stevens, Dale; Sonoda, Junichiro; Cowan, Kyra; Boswell, C. Andrew; Stefanich, Eric
ABSTRACT: Target receptor levels can influence pharmacokinetics (PK) or pharmacodynamics (PD) of monoclonal antibodies (mAbs), and can affect drug development of this class of molecules. We generated an effector-less humanized bispecific antibody that selectively activates fibroblast growth factor receptor (FGFR)1 and βKlotho receptor, a FGF21 receptor complex highly expressed in both white and brown adipocytes. The molecule shows cross-species binding with comparable equilibrium binding affinity (Kd) for human, cynomolgus monkey, and mouse FGFR1/βKlotho. To understand the PK/PD relationship in non-obese and obese animals, we evaluated the adipose tissue distribution of the antibody, serum exposures, and an associated PD marker (high-molecular-weight adiponectin), in both non-obese and obese mice and monkeys. Antibody uptake into fat tissue was found to be higher on a per gram basis in non-obese animals compared to obese animals. Since obesity has been reported to be associated with reduced expression of FGFR1 and βKlotho receptor in white adipose tissues in mice, our results suggest that the distribution in adipose tissues was influenced by target expression levels. Even so, the overall dose-normalized serum exposures were comparable between non-obese and obese mice and monkeys, suggesting that adipose tissue uptake plays a limited role in overall systemic PK determination. It remains to be determined if and how obesity and receptor expression in humans influence the PK and PD profile of this novel therapeutic candidate.